Functionalized cyclodextrins. Synthesis and structural characterization of 6-deoxy-6-{4-[2-(N-tert-butoxycarbonyl)aminoethyl]imidazolyl}cyclomaltoheptaose - Di Blasio, Benedetto; Galdiero, Stefania; Saviano, Michele; De Simone, Giuseppina; Benedetti, Ettore; Pedone, Carlo; Gibbons, William A.; Deschenaux, Robert; Rizzarelli, Enrico; Vecchio, Graziella (My University, 1996)
The synthesis and crystal structure of the title ?-cyclodextrin (?-CD) are reported. It crystallizes in the orthorhombic space group P212121 [a 17.250(9), b 19.45(1), c 23.24(1) Å, dcalc 1.304 g/cm3, Z 4]. The structure was refined to final indexes R1 = 0.083 and wR2 = 0.24 for the 4843 obsd. reflections with I ? 2?(I). At the end of the refinement the presence of 12 H2O mols. per ?-CD mol. distributed over 16 sites was detected. In the solid state the monofunctionalized ?-CD shows a "sleeping swan"-like shape with the covalently bound (Boc-aminoethyl)imidazolyl moiety forming a folded structure with its terminal part inserted inside the hydrophobic cavity of the ?-CD ring. The ?-CD macrocycle presents only small differences with respect to the conformation obsd. in hydrated uncomplexed or methylated ?-CDs. The macrocycle structure maintains an approx. 7-fold symmetry. The substituted ?-CD mols. pack in layers parallel to the bc plane. The layers are stacked in an head-to-tail arrangement of the monomeric units, with formation of columns of mols. along the a axis. The layers are connected to each other by H-bonds through H2O mols. Channels generated in the crystal by the packing of the macrocycles are filled with H2O mols. [on SciFinder(R)]
Keywords: aminoethylimidazolylcyclodextrin prepn crystal structure; cyclodextrin aminoethylimidazolyl prepn crystal structure